Effect of wall stiffness, mass and potential interaction strength on heat transfer characteristics of nanoscale-confined gas. (February 2020) - Rabani, Reza; Heidarinejad, Ghassem; Harting, Jens; Shirani, Ebrahim
Highlights: Molecular Dynamics Simulation is applied to investigate nanoconfined rarefied gas. A wide range of wall material properties has been considered in the simulation. Prediction of heat transfer through the gas medium for metal walls is presented. Abstract: The interactive thermal wall model is applied in three-dimensional molecular dynamics simulations to investigate the combined effect of the wall force field, the wall stiffness, the wall atom mass and the wall/gas interaction potential strength on the heat transfer characteristics of static rarefied argon gas within a nanochannel. By increasing the wall stiffness, a reduction in the heat flux through the gas medium occurs which leads to a higher temperature jump. As the wall atom mass is increased up to twice the argon atom mass, the heat flux is enhanced notably and a minimum temperature jump can be found at this point. Further increase in the wall atom mass results in reducing the heat flux and consequently increasing the temperature jump. The increment of the wall/gas interaction potential strength up to four times the one of gas/gas interactions is shown to enhance the heat flux and to reduce the temperature jump until it eventually vanishes. Furthermore, it is found that under such conditions, the density profile experiences a second peak. A further increase of this parameter is found to have a negligible effect on the heat flux through the gas medium and it only increases the second peak in the density profile.